PlrA (MSMEG_5223) is an essential polar growth regulator in Mycobacterium smegmatis. - Samantha Y Quintanilla; Neda Habibi Arejan; Parthvi B Patel; Cara C Boutte (PLoS ONE, 2023)
Mycobacteria expand their cell walls at the cell poles in a manner that is not well described at the molecular level. In this study, we identify a new polar factor, PlrA, that is involved in restricting peptidoglycan metabolism to the cell poles in Mycobacterium smegmatis. We establish that only the N-terminal membrane domain of PlrA is essential. We show that depletion of plrA pheno-copies depletion of polar growth factor Wag31, and that PlrA is involved in regulating the Wag31 polar foci.